Jus Punica Granatum Memulihkan Motilitas Spermatozoa Tikus Putih Pada Kondisi Stres Oksidatif - Putu Oky Ari Tania; Emilia Devi D. Rianti; Indra Firismanda Dermawan; Nur Sri Wahyuni (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
Fast food consumption including used of repeated heating-oil, causing various of health problems, especially the formation of free radicals characterized by elevated MDA levels. Pomegranates have many therapeutic functions, especially as antioxidants that scavenges free radical of oxidative stress thus improving the quality of spermatozoa. The aim of this study was to see the effect of pomegranate juice to reduce oxidative stress and improve sperm motility. This study used 24 rats divided into 4 groups, namely KN, KP, JD1 and JD2. The mean MDA content (nmol / ml) in KN, KP, JD1 and JD2 was 23.35; 8,53; 12.15; and 12,83 followed by Kruskal-Wallis test obtained p value 0,021 (p <0,05). The quality of spermatozoa includes the motility of spermatozoa which distinguished 4 criteria: fast moving spermatozoa and straight forward (criteria 1), spermatozoa move slowly / difficult to go straight (criteria 2), street spermatozoa (criteria 3) and immobile spermatozoa (criteria 4). Mean percentage (%) number of spermatozoa criteria 1 on KN, KP, JD1, and JD2 among others 41,6; 18.2; 38; and 62.2. Mean percentage (%) number of spermatozoa criteria 2 on KN, KP, JD1, and JD2 among others 4,4; 21.8; 15.6 and 14.2. Mean of percentage (%) motility of spermatozoa criteria 3 on KN, KP, JD1, and JD2 among others 10.6; 24.8; 11.2 and 15.2, while for criteria 4 is 21.8; 37.2; 40.4; and 13.8. Statistical test for sperm motility using ANOVA one way, on criteria 1, 2, 3 and 4 each got p value 0,000; 0.010; 0,000; and 0.000, which means the administration of pomegranate juice shows the effect on the motility of spermatozoa.